Fimbriation genes of Salmonella enteritidis. - Müller, K H (1989)
From a cosmid clone, a 5.3-kilobase (kb) HindIII fragment of Salmonella enteritidis DNA containing the fimA gene was subcloned into bacteriophage T7 promoter vectors in both orientations. Predominantly mature fimbrin (14,000 Mr) was produced by clones containing the 5.3-kb insert, whereas the original cosmid clone predominantly accumulated a prefimbrin precursor (16,500 Mr). T7 RNA polymerase-dependent expression of the 5.3-kb insert and of a series of nested deletions revealed several membrane-localized polypeptides (80,000, 40,000, 29,000, 25,000, and 16,500 Mrs) transcribed in the same direction as fimA as well as a single polypeptide (9,000 Mr) transcribed in the opposite direction. Mini-Mu and TnphoA (Tn5 IS50L::phoA) transposon mutagenesis was used to identify a 2- to 3.5-kb region downstream of fimA that affected fimbrin production and processing. A more distant region (greater than 7 kb), revealed by Tn10 and Mu dI mutagenesis, was also required for fimbriation but did not hybridize with the 5.3-kb fragment. Yet another distant region did hybridize to the 5.3-kb fragment, suggesting the existence of other fimbriation-related genes.